2022
DOI: 10.1002/nop2.1528
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the humour styles questionnaire in healthcare professionals

Abstract: Aim The aim of this study is to determine the reliability and validity of the Humour Styles Questionnaire (HSQ) in a sample of Spanish healthcare professionals. Design A cross‐sectional study. Methods The version of HSQ translated into Spanish by Cayssials and Pérez was used to validate on a sample of healthcare professionals (N = 250). The reliability analysed the Crombach's α coefficient and Pearson's correlation coefficient between the factors and the total scale score. The Exploratory Factor Analysis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(86 reference statements)
0
0
0
1
Order By: Relevance
“…With regard to gender differences, males scored significantly higher on all four humor styles, especially on Aggressive, supporting the evolutionary based hypothesis (Greengross & Miller, 2011), which states that males generally use humor more frequently. The observed gender differences are also in a line with Martin's original data (Martin et al, 2003) and consistent to previous results with Spanish samples (Schermer et al, 2023;Salavera et al, 2020;Leñero-Cirujano et al, 2022). The results also showed that younger participants score higher on all humor styles scales.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With regard to gender differences, males scored significantly higher on all four humor styles, especially on Aggressive, supporting the evolutionary based hypothesis (Greengross & Miller, 2011), which states that males generally use humor more frequently. The observed gender differences are also in a line with Martin's original data (Martin et al, 2003) and consistent to previous results with Spanish samples (Schermer et al, 2023;Salavera et al, 2020;Leñero-Cirujano et al, 2022). The results also showed that younger participants score higher on all humor styles scales.…”
Section: Discussionsupporting
confidence: 91%
“…Satisfactory internal consistency of the scales was very similar to that reported by Martin et al (2003), as well as results obtained in Spanish samples , Leñero-Cirujano et al, 2022, indicating cross-cultural reliability across different countries and samples. Exploratory factor analysis yielded similar results to those of the original study (Martin et al, 2003), as well as in studies with Spanish samples (Leñero-Cirujano et al, 2022;Schermer et al, 2023;Torres-Marín, et al, 2018). Four-factor structure of the HSQ, robust goodness of fit statistics, as well as good factors' reliability were provided.…”
Section: Discussionsupporting
confidence: 81%
“…Higher scores in each dimension indicate a higher level of that particular humor style. The Spanish version of the HSQ demonstrated an internal consistency of 0.7516 to 0.8217 and a common variance of 41.60%16to 44.46% 17. We obtained permission from the original author via email to use this scale.…”
Section: Methodsmentioning
confidence: 99%
“…En la actualidad existen escalas que evalúan este fenómeno en la población general desde una perspectiva sociocultural, tales como la Escala de Adaptación al Humor, 22 el Cuestionario de Respuesta Humorística Situacional, 23 el Cuestionario del Sentido del Humor, 24 la Escala Multidimensional del Sentido del Humor 25 o el Cuestionario de Estilos de Humor, 26 siendo esta última validada en profesionales sanitarios. 27 No obstante, ninguna de ellas valora el humor en el contexto sanitario. Es precisamente en esta línea en la que se pretende situar el foco de investigación, en cómo el profesional puede llegar a generar y apreciar el humor no solo en su vida privada, sino también en su vida laboral y en la relación con el paciente y su entorno.…”
Section: Introductionunclassified